2001
DOI: 10.1001/jama.285.20.2604
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Increasing β-Blocker Use After Myocardial Infarction

Abstract: This study provides a context for understanding efforts to improve care in the hospital setting by describing a taxonomy for classifying and evaluating such efforts. In addition, the study suggests possible elements of successful efforts to increase beta-blocker use for patients with AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…Components of adopting and implementing recommended TUT ( Bradley et al, 2001, Fiore et al, 2008, Partnership for Prevention, 2008 and the percent of responding centers reporting these can be found in Figure 2 . Other than providing tobacco education materials, no recommended TUT practice was found in more than 60% of Cancer Centers.…”
Section: Current Cancer Center Policy and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Components of adopting and implementing recommended TUT ( Bradley et al, 2001, Fiore et al, 2008, Partnership for Prevention, 2008 and the percent of responding centers reporting these can be found in Figure 2 . Other than providing tobacco education materials, no recommended TUT practice was found in more than 60% of Cancer Centers.…”
Section: Current Cancer Center Policy and Practicementioning
confidence: 99%
“…Giving feedback to individual physicians or clinics on the care they provide has shown to be effective in changing physician behavior ( Bradley et al, 2001 ). Cancer Center administrators should work with information technology staff to produce reports on tobacco use identification and treatment for feedback to providers and the institution.…”
Section: Tobacco Use Treatment At Us Nci Cancer Centersmentioning
confidence: 99%
“…Early lessons about translating findings into practice are being called into question based on more recent reviews and evolving research [19,30,31]. There are now calls both for better theoretical underpinnings for implementation interventions at the individual provider level and for better information about the critical influence of organizational context [11,19,32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bradley et al studied hospital efforts to improve use of β-blockers [30]. They found that the presence of shared goals for quality improvement (QI), use and availability of credible feedback data for monitoring improvements, and the degree of support from hospital administration and clinical leadership – per related advocacy for the EBP – were key factors in differentiating high versus low performance.…”
Section: Introductionmentioning
confidence: 99%
“…Taking beta-blockers after hospitalization for myocardial infarction reduces morbidity and costs in the short term, period. [2][3][4][5] Flu shots reduce the average medical claim costs per individual immunized by between $16 and $60 per member per year. [6][7][8][9] What one might question is whether the infrastructure developed by a health plan or DM company is as effective as a university study group.…”
Section: Introduction B Enefit Managers Particularly In Smallermentioning
confidence: 99%